IL-27 Counteracts Neuropathic Pain Development Through Induction of IL-10 - Fonseca, Miriam M.; Davoli-Ferreira, Marcela; Santa-Cecília, Flávia; Guimarães, Rafaela M.; Oliveira, Francisco F. B.; Kusuda, Ricardo; Ferreira, David W.; Alves-Filho, José C.; Cunha, Fernando Q.; Cunha, Thiago M. (Frontiers in Immunology, 2020)
Neuroimmune-glia interactions have been implicated in the development of neuropathic pain. Interleukin-27 (IL-27) is a cytokine that presents regulatory activity in inflammatory conditions of the central nervous system (CNS). Thus, we hypothesized that IL-27 would participate in the neuropathic pain process. Here, we found that neuropathic pain caused by peripheral nerve injury (spared nerve injury model; SNI), was enhanced in IL-27 deficient (-/-) mice, whereas nociceptive pain is similar to wild type mice. SNI induced an increase in the expression of IL-27 and its receptor subunit (Wsx1) in the sensory ganglia and spinal cord. IL-27 receptor was expressed mainly in resident macrophage, microglia and, astrocytes of the sensory ganglia and spinal cord, respectively. Finally, we identify that the antinociceptive effect of IL-27 was not observed in IL-10-/- mice. These results provided evidence that IL-27 is a cytokine produced after peripheral nerve injury that counteracts neuropathic pain development through induction of the antinociceptive cytokine IL-10. In summary, our study unraveled the role of IL-27 as a regulatory cytokine that counteracts the development of neuropathic pain after peripheral nerve damage. In conclusion, they indicate that immunotherapies based on IL-27 could emerge as possible therapeutic approaches for the prevention of neuropathic pain development after peripheral nerve injury.